Вы находитесь на странице: 1из 6

TRANSITION FROM

QUANTUM TO CLASSICAL
MECHANICS

V. G. BAGROV

. .

The role of the semiclassical approximation in


course of foundation and
development of quantum
mechanics as well as
some ideas underlying the
semiclassical are explained.
fl fl fl

fl, .


. , 18 1899
. , , , , -
, . 19 1900 .
, . 14
1900 . ,


,
(). E
:
E = ",

(1)

" . (18 1889 )


1.
,
, . ,
. . , , , -, . . , .
. 1905 , ()2,

.., 1999

110

.
, = 2. (1)
. E = h, h = 2". (1) ".
2
. ,

(1),
() .

. . .
. .

, 6, 1999

,
,
. . 1906 . ,
1912 . , . .
, 1913
. , .

. .

,

. -, ,
( ),
S
" 1
1
S = 2" n + --- ,

n = 0, 1, 2, 3, ;

(2)

-,
, E1 E2 ( )
E1 E2 = ".

(3)

, . ,
. , , .

. 19141921
. 19211926 (. , . , . ).
. , .
,



- .
, , ,

,
.
1
. (2) S = 2"n.
, .
(2).

-
( , - ),
,
, .
,
.
.
().
() . -
, .

, ,
() ,
, - , ; - , ,
, ;

, .
- ,
- , . ,
, ,

. ,
, , , .


. , , , , .
, , ( ).
, ,
,
.

: , (
),
.

..

111


, .

1926 . ,
(
).
,
.
,
-
.
.
,
.
.

.
(). ,
, .
- ,
, , ,
.
.
1926 , .

,

.
.
.

, , ,
.

.
". ,

, "2,

112

". ,
,

.
" 1 ( ") . ,

0
"
, (
") , (, ).
, (" =
= 0) .
. ,
" = 0 ( )
.
,

". (. , . , . , 1926 ) .
, .
,
. . ,
,
,
. , , ,
, , .

,
, , .
"
( )
, "
, , - " ,
,
". ,
.
1

, 6, 1999

( ..
), .
, - (
, )
.. .

. . :
. , , ,
. , 0)
("
.
? , . - , "
0 ,
"
. ,
-
.
, ,
"
0 .
, , ,
. .

, . x
x = x(t).
?
.
x x . x , , , ",
0 x = x (t, "). "
( ) x = x (t), , -,
x(t) = x (t). ,
.
-. x(t) ( ).
0
- "
.
?
,
. , -

, ,
. , ,
()
, . ,


.

(1927 ). . , .
, (

).
.
, ,
. , ,
( ), . .
60- , , ,
, ,
( ). ,
,
.


(.. , .. , 1969 ),

(.. , .. , .. , 1982 )

.. (
). ,
()
,
, .
,

.

..

113


.
( )
, . A
.
, , x p,
A = A(x, p)

(4)

x p.
x = x + x,
x = x x,

p = p + p,
p = p p,

(5)

x, p .
, x x ( t ), p p ( t ), x(t), p(t) , x p - (,
).
A = A ( x, p ) = A ( x + x, p + p )

(6)

x, p ( x, p) .
x, p,
, , A x, p
( )
x, p ( ).

x, p .
, ( ). ,
x, p :
x " ,

p ".

(7)

, - "n,
2n,

(,
).
.
:
", (
)

114


(
"
). ,
( )
.

. (2)1.
,

, A, x ( ).
x = 0 .
x t
= t + .

x(t) = Asin,

(8)

(t) p(t)
m
dx ( t )
( t ) = ------------ = A cos ,
dt
p ( t ) = m ( t ) = mA cos .

(9)

E E1(t) E2(t):
m ( t ) p ( t )
E 1 ( t ) = ----------------- = ------------ ,
2
2m
2

m x ( t )
E 2 ( t ) = ----------------------- ,
2

2 2

2
p ( t ) m x ( t )
E = E 1 ( t ) + E 2 ( t ) = ------------ + ----------------------- .
2
2m
2 2

(10)

(10) (8) (9),


2

m A
E = ----------------- ,
2

(11)

( ) A
E.
(2)

1 2
S = p d x = p dt = ---- p dt,
m

(12)

(
T =
= 2/). (12) (9) (11),
1
.
.
.

, 6, 1999

S = m A cos dt = m A
2

T
2

cos d =
2

1. . . .: , 1985.

(13)

2E
2
= m A = ----------.

2. . . .: ,
1990.
3. ..
XX . .: , 1986.

(13) (2)
1
E = " n + --- .

4. . // . .:
, 1975.

(14)

5. . . .: , 1971.
. 2.

, - ( ) .

6. ..
( , ,
) // . 1996. 7. . 8188.

( )
, . :
,
( )
, , .
, - ,
, ,
. [6],
, .

7. . . .: ,
1965. . 134148, 170188.
8. .. . .:
, 1987. (. ; 3).
9. .. . .: , 1989. (- ; . 75).
10. .. . .: ,
1989.

* * *
, , -, ,
.
.
, ,
,
. 350 , .

..

115